Battery cell with large grain boundary and pre-lithiated aluminum anode electrode
By rolling and annealing the aluminum foil layer, combined with aging/pre-lithiation processes, a large grain boundary aluminum anode electrode is formed, which solves the problem of poor initial coulombic efficiency and capacity transport of the aluminum anode electrode, and significantly improves the performance of the battery pack.
Patent Information
- Application Number
- CN202410748594.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2025-12-12
AI Technical Summary
Existing aluminum anode electrodes in battery packs suffer from low initial coulombic efficiency and poor capacity delivery, especially after pre-lithiation, due to diffusion capture of active lithium and mechanical fracture, resulting in poor performance.
The aluminum foil layer is rolled and annealed to increase the grain boundary sharpness, and the aluminum foil layer is transformed into a lithium-aluminum layer through an aging/pre-lithiation process to form large grain boundaries and a pre-lithiated aluminum anode electrode, which promotes the diffusion of lithium ions in the anode.
It improves the initial coulombic efficiency and capacity delivery of the battery pack, and enhances the cycle performance of the battery, especially in the all-solid-state battery pack, where it exhibits an initial coulombic efficiency of 86% and a capacity delivery of 143 mAh/g.
Smart Images

Figure CN121123355A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to battery packs, and more particularly to battery packs including pre-lithiated aluminum anode electrodes. Background Technology
[0002] The information provided in this section is intended to provide a general overview of the background of this disclosure. The work of the currently named inventors described in this section, and the aspects of the specification that may not have been otherwise identified as prior art at the time of filing, are not expressly or impliedly acknowledged as prior art to this disclosure.
[0003] Electric vehicles (EVs), such as battery electric vehicles (BEVs), hybrid electric vehicles, and / or fuel cell vehicles, include one or more motors and battery pack systems, said battery pack system including one or more battery cells, modules, and / or packs. A power control system is used to control the charging and / or discharging of the battery pack system during charging and / or driving.
[0004] The battery pack includes a cathode electrode, an anode electrode, and a separator. The cathode electrode includes a layer of cathode active material disposed on a cathode current collector. The anode electrode includes a layer of anode active material disposed on an anode current collector. Summary of the Invention
[0005] A battery pack includes C cathode electrodes, A anode electrodes, and S separators, where A, C, and S are integers. Each of the A anode electrodes includes an annealed aluminum foil layer and a lithium-aluminum layer disposed on one side of the annealed aluminum foil layer.
[0006] Among other features, the S separators comprise a solid electrolyte. The C cathode electrodes comprise a cathode active material layer disposed on one or both sides of the cathode current collector, the cathode active material layer comprising cathode active material and solid electrolyte.
[0007] Among other features, the solid electrolyte is selected from sulfide solid electrolytes, oxide-based solid electrolytes, metal-doped or anisovalent substituted oxide solid electrolytes, nitride-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, borate-based solid electrolytes, and combinations thereof.
[0008] Among other features, the battery pack includes all-solid-state battery packs.
[0009] Among other features, the S isolation elements comprise a solid electrolyte and a liquid electrolyte, the C cathode electrodes comprise a cathode active material layer comprising a cathode active material, a solid electrolyte, and a liquid electrolyte, and the cathode active material layer is disposed on one or both sides of the cathode current collector.
[0010] Among other features, the solid electrolyte is selected from sulfide solid electrolytes, oxide-based solid electrolytes, metal-doped or anisovalent substituted oxide solid electrolytes, nitride-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, borate-based solid electrolytes, and combinations thereof.
[0011] Among other features, the C cathode electrodes include a cathode active material layer comprising a cathode active material and a liquid electrolyte; and the S separators include a separator layer.
[0012] Among other features, the spacer layer is selected from polyolefin-based spacers, cellulose spacers, polyvinylidene fluoride (PVDF) membranes, porous polyimide membranes, and ceramic-coated spacers.
[0013] Among other features, the insulating layer is selected from nonwoven fabrics based on polyimide (PI) nanofibers, polyethylene films coated with nano-scale Al2O3 and poly(lithium 4-styrene sulfonate), SiO2-coated polyethylene (PE) insulating elements, copolyimide-coated polyethylene insulating elements, polyetherimide (PEI) insulating elements, expanded polytetrafluoroethylene-reinforced polyvinylidene fluoride-hexafluoropropylene insulating elements, and sandwich-structured PVdF / PMIA / PVdF nanofiber insulating elements.
[0014] Among other features, the C cathode electrodes comprise cathode active materials selected from layered oxides, olivine oxides, monoclinic oxides, spinel oxides, tavorite, sulfur, Li2S, and combinations thereof.
[0015] A battery pack includes C cathode electrodes, A anode electrodes, and S separators, where A, C, and S are integers. Each of the A anode electrodes includes an annealed aluminum foil layer, a lithium-aluminum layer disposed on one side of the annealed aluminum foil layer, and a copper current collector disposed on one side of the lithium-aluminum layer.
[0016] Among other features, the C cathode electrodes include a cathode active material layer comprising a cathode active material and a solid electrolyte. The solid electrolyte is selected from sulfide solid electrolytes, oxide-based solid electrolytes, metal-doped or anisovalent substituted oxide solid electrolytes, nitride-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, borate-based solid electrolytes, and combinations thereof.
[0017] Among other features, the S separators comprise a solid electrolyte. The solid electrolyte is selected from sulfide solid electrolytes, oxide-based solid electrolytes, metal-doped or anisovalent substituted oxide solid electrolytes, nitride-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, borate-based solid electrolytes, and combinations thereof.
[0018] Among other features, the C cathode electrodes include a cathode active material layer comprising a cathode active material and a liquid electrolyte, and the S separators include a separator layer. The separator layer is selected from polyolefin-based separators, cellulose separators, polyvinylidene fluoride (PVDF) membranes, porous polyimide membranes, and ceramic-coated separators.
[0019] Among other features, the insulating layer is selected from nonwoven fabrics based on polyimide (PI) nanofibers, polyethylene films coated with nano-scale Al2O3 and poly(lithium 4-styrene sulfonate), SiO2-coated polyethylene (PE) insulating elements, copolyimide-coated polyethylene insulating elements, polyetherimide (PEI) insulating elements, expanded polytetrafluoroethylene-reinforced polyvinylidene fluoride-hexafluoropropylene insulating elements, and sandwich-structured PVdF / PMIA / PVdF nanofiber insulating elements.
[0020] Among other features, the C cathode electrodes comprise cathode active materials selected from layered oxides, olivine oxides, monoclinic oxides, spinel oxides, tavorite, sulfur, Li2S, and combinations thereof.
[0021] The present invention discloses the following solutions:
[0022] Option 1. A battery pack comprising:
[0023] C cathode electrodes;
[0024] A anode electrode; and
[0025] There are S isolation components, where A, C, and S are integers.
[0026] Each of the A anode electrodes comprises:
[0027] Annealed aluminum foil layer; and
[0028] A lithium-aluminum layer disposed on one side of the annealed aluminum foil layer.
[0029] Option 2. The battery pack according to Option 1, wherein...
[0030] The S separators contain solid electrolytes.
[0031] The C cathode electrodes include a cathode active material layer disposed on one or both sides of the cathode current collector, the cathode active material layer comprising cathode active material and solid electrolyte.
[0032] Option 3. The battery pack according to Option 2, wherein the solid electrolyte is selected from sulfide solid electrolytes, oxide-based solid electrolytes, metal-doped or anisovalent substituted oxide solid electrolytes, nitride-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, borate-based solid electrolytes, and combinations thereof.
[0033] Option 4. The battery pack according to Option 2, wherein the battery pack includes an all-solid-state battery pack.
[0034] Option 5. The battery pack according to Option 1, wherein...
[0035] The S separators comprise solid electrolytes and liquid electrolytes.
[0036] The C cathode electrodes each include a cathode active material layer, which comprises a cathode active material, a solid electrolyte, and a liquid electrolyte.
[0037] The cathode active material layer is arranged on one or both sides of the cathode current collector.
[0038] Option 6. The battery pack according to Option 5, wherein the solid electrolyte is selected from sulfide solid electrolytes, oxide-based solid electrolytes, metal-doped or anisovalent substituted oxide solid electrolytes, nitride-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, borate-based solid electrolytes, and combinations thereof.
[0039] Option 7. The battery pack according to Option 1, wherein...
[0040] The C cathode electrodes each include a cathode active material layer, the cathode active material layer comprising a cathode active material and a liquid electrolyte; and
[0041] The S isolation components include isolation component layers.
[0042] Option 8. The battery pack according to Option 7, wherein the separator layer is selected from polyolefin-based separators, cellulose separators, polyvinylidene fluoride (PVDF) membranes, porous polyimide membranes, and ceramic-coated separators.
[0043] Option 9. The battery pack according to Option 7, wherein the separator layer is selected from nonwoven fabric based on polyimide (PI) nanofibers, polyethylene film coated with nano-scale Al2O3 and poly(lithium 4-styrene sulfonate), SiO2 coated polyethylene (PE) separator, copolyimide coated polyethylene separator, polyetherimide (PEI) separator, expanded polytetrafluoroethylene reinforced polyvinylidene fluoride-hexafluoropropylene separator, and sandwich structure PVdF / PMIA / PVdF nanofiber separator.
[0044] Option 10. The battery pack according to Option 1, wherein the C cathode electrodes comprise cathode active materials selected from layered oxides, olivine oxides, monoclinic oxides, spinel oxides, tavorite, sulfur, Li2S, and combinations thereof.
[0045] Option 11. A battery pack comprising:
[0046] C cathode electrodes;
[0047] A anode electrode; and
[0048] There are S isolation components, where A, C, and S are integers.
[0049] Each of the A anode electrodes comprises:
[0050] Annealed aluminum foil layer;
[0051] A lithium-aluminum layer disposed on one side of the annealed aluminum foil layer; and
[0052] A copper current collector is disposed on one side of the lithium-aluminum layer.
[0053] Option 12. The battery pack according to Option 11, wherein the C cathode electrodes include a cathode active material layer, the cathode active material layer comprising a cathode active material and a solid electrolyte.
[0054] Option 13. The battery pack according to Option 12, wherein the solid electrolyte is selected from sulfide solid electrolytes, oxide-based solid electrolytes, metal-doped or anisovalent substituted oxide solid electrolytes, nitride-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, borate-based solid electrolytes, and combinations thereof.
[0055] Option 14. The battery pack according to Option 11, wherein the S separators comprise a solid electrolyte.
[0056] Option 15. The battery pack according to Option 14, wherein the solid electrolyte is selected from sulfide solid electrolytes, oxide-based solid electrolytes, metal-doped or anisovalent substituted oxide solid electrolytes, nitride-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, borate-based solid electrolytes, and combinations thereof.
[0057] Option 16. The battery pack according to Option 11, wherein:
[0058] The C cathode electrodes each include a cathode active material layer, which comprises a cathode active material and a liquid electrolyte.
[0059] The S isolation components include isolation component layers.
[0060] Option 17. The battery pack according to Option 16, wherein the separator layer is selected from polyolefin-based separators, cellulose separators, polyvinylidene fluoride (PVDF) membranes, porous polyimide membranes, and ceramic-coated separators.
[0061] Option 18. The battery pack according to Option 16, wherein the separator layer is selected from nonwoven fabric based on polyimide (PI) nanofibers, polyethylene film coated with nano-scale Al2O3 and poly(lithium 4-styrene sulfonate), SiO2 coated polyethylene (PE) separator, copolyimide coated polyethylene separator, polyetherimide (PEI) separator, expanded polytetrafluoroethylene reinforced polyvinylidene fluoride-hexafluoropropylene separator, and sandwich structure PVdF / PMIA / PVdF nanofiber separator.
[0062] Option 19. The battery pack according to Option 11, wherein the C cathode electrodes comprise cathode active materials selected from layered oxides, olivine oxides, monoclinic oxides, spinel oxides, tavorite, sulfur, Li2S, and combinations thereof.
[0063] The further applicability of this disclosure will be apparent from the detailed description, claims, and drawings. The detailed description and specific embodiments are intended to be illustrative only and are not intended to limit the scope of this disclosure. Attached Figure Description
[0064] This disclosure will be more fully understood from the detailed description and the accompanying drawings, in which:
[0065] Figure 1 This is a side cross-sectional view of an example of a battery pack according to the present disclosure;
[0066] Figure 2 and Figure 3 These are side cross-sectional views of an example of an anode electrode according to this disclosure before and after aging / pre-lithiation;
[0067] Figure 4 , Figure 5 , Figure 6 , Figure 7 , Figure 8 and Figure 9 This is a side cross-sectional view of an example of a battery pack including a pre-lithiated aluminum anode electrode according to the present disclosure;
[0068] Figure 10 The molecular structures of aluminum foil and annealed pre-lithiated aluminum foil according to the present disclosure are shown.
[0069] Figure 11A and 11B Examples of grain boundary distribution (>15°) of aluminum foil and annealed aluminum foil according to this disclosure are shown respectively;
[0070] Figure 12 An example of a lithium-ion diffusion path within a LiAl alloy according to this disclosure is shown;
[0071] Figure 13 It is a voltage vs. capacity graph of pre-lithiated aluminum foil and annealed pre-lithiated aluminum foil according to this disclosure; and
[0072] Figure 14 It is a capacity vs. cycle diagram of pre-lithiated aluminum foil and annealed pre-lithiated aluminum foil according to this disclosure.
[0073] In the accompanying drawings, reference numerals may be reused to designate similar and / or identical elements. Detailed Implementation
[0074] Although the battery packs according to this disclosure are shown in the context of electric vehicles, the battery packs can be used in stationary applications and / or other applications.
[0075] Aluminum has attracted attention as an anode active material for battery packs, such as high-energy-density all-solid-state batteries (ASSB). Aluminum is abundant and inexpensive, and possesses a suitable operating potential (~0.3V vs Li). + The theoretical capacity of aluminum is 990 mAh / g (from Al (α phase, fcc) to LiAl (β phase, cubic), with a volume change of 96%, lower than the 310% volume change of silicon anode electrodes. However, even after pre-lithiation, aluminum exhibits poor initial coulombic efficiency and capacity delivery, likely due to diffusion trapping and mechanical fracture of active lithium.
[0076] This disclosure relates to an aluminum anode active material layer for the anode electrode of a battery pack (e.g., an ASSB battery, a semi-solid-state battery pack, or a liquid electrolyte-based battery pack). According to this disclosure, the aluminum foil is rolled and then annealed to refine the aluminum grains and increase the sharpness of the grain boundaries (GBs).
[0077] Annealed aluminum foil is mechanically bonded to other layers of the anode electrode using a rolling process, followed by aging / pre-lithiation. Using annealed aluminum foil effectively increases GB distribution and promotes lithium-ion diffusion within the anode electrode. Pretreatment triggers a spontaneous transition from the α-phase (Al structure) to the β-phase (LiAl), compensating for active lithium loss and enhancing battery cycling.
[0078] The aluminum foil layer is rolled once or multiple times to ensure precise control over the foil's thickness and shape. In some instances, the rolled aluminum foil layer thickness is from 2 μm to 80 μm. In some instances, the rolled aluminum foil layer thickness is from 30 μm to 50 μm (e.g., 40 μm). In some instances, the aluminum foil layer contains 94.0 wt% to 99.99 wt% aluminum. In some instances, the aluminum foil layer contains 98.0 wt% to 99.95 wt% aluminum (e.g., 99 wt%).
[0079] After rolling, the aluminum foil layer is annealed. During annealing, recrystallization and polygonization begin to refine the grains and increase the sharpness of the grain boundaries. In some examples, annealing is performed at temperatures ranging from 250°C to 550°C. In some examples, annealing is performed at temperatures ranging from 300°C to 400°C (e.g., 350°C). In some examples, the annealing period is from 10 minutes to 24 hours. In some examples, the annealing period is from 30 minutes to 90 minutes (e.g., 60 minutes).
[0080] In some instances, the grain boundary distribution (>15°) after annealing is between 46% and 80%. In other instances, the grain boundary distribution (>15°) after annealing is between 60% and 70% (e.g., 65%). After rolling and annealing, the aluminum foil layer is mechanically bonded to other layers (e.g., one or more lithium metal foil layers and / or separator layers).
[0081] Large grain boundaries and pre-lithiated aluminum anode electrodes enhance the performance of battery packs such as ASSB. The battery pack exhibits enhanced initial coulombic efficiency (86%) and increased capacity delivery (143 mAh / g at 0.1C).
[0082] Now for reference Figure 1The battery pack 10 includes C cathode electrodes 20, A anode electrodes 40, and S separators 32 arranged in a predetermined order within the battery pack stack 12, where C, S, and A are integers greater than zero. The battery pack stack 12 is disposed within a housing 50. The C cathode electrodes 20-1, 20-2, ..., and 20-C include a cathode active material layer 24 disposed on one or both sides of the cathode current collector 26. The A anode electrodes 40-1, 40-2, ..., and 40-A include an anode active material layer 42 and an anode current collector 46.
[0083] During charging / discharging, A anode electrodes 40 and C cathode electrodes 20 exchange lithium ions. In some instances, the cathode active material layer 24 includes a coating applied to the current collector, the coating comprising one or more active materials, one or more conductive additives, and / or one or more binder materials. In some instances, S separators include a solid electrolyte or a separator layer.
[0084] In some instances, the cathode current collector 26 comprises metal foil, metal mesh, perforated metal, 3D metal foam, and / or expanded metal. In some instances, the cathode current collector is made of one or more materials selected from stainless steel, aluminum, and / or alloys thereof. External tabs 28 and 48 are connected to the current collectors of the cathode and anode electrodes, respectively, and may be arranged on the same or different sides of the battery pack stack 12. External tabs 28 and 48 are connected to the terminals of the battery pack cells.
[0085] Now for reference Figure 2 and Figure 3 An example of an anode electrode 120 according to this disclosure is shown during processing. The anode electrode 120 includes lithium metal foil layers 112 and 116 disposed on opposite sides of an annealed aluminum foil layer 114. In some embodiments, the annealed aluminum foil layer 114 is rolled (pressed and / or heated) using rollers before annealing and mechanical bonding with other layers such as the lithium metal foil layers 112 and 116. The aluminum foil layer 114 is rolled once or multiple times to ensure precise control of foil thickness and shape. The lithium metal foil layers 112 and 116 are mechanically bonded to opposite sides of the aluminum foil layer 114 using a rolling process.
[0086] exist Figure 3 In this process, aluminum foil layer 114 and lithium metal foil layers 112 and 116 are aged for a predetermined period after mechanical bonding to allow pre-lithiation to occur. The lithium metal foil layers 112 and 116 are pre-lithiated to form lithium aluminum (LiAl) layers 122 and 126 disposed on opposite sides of aluminum foil layer 114.
[0087] It is understood that the anode electrode may include other arrangements of the layers. For example, the anode electrode may include a rolled and annealed aluminum foil layer disposed on the side of the lithium metal foil layer. The layers are mechanically bonded together using a similar process, and the lithium metal foil layer is converted into a lithium-aluminum layer using aging / pre-lithiation.
[0088] In other examples, the anode electrode may comprise a rolled and annealed aluminum foil layer disposed on the sides of the first and second lithium metal foil layers. The first and second lithium metal foil layers are disposed on opposite sides of the anode current collector (e.g., a copper foil layer). The layers are mechanically bonded together using a similar process, and the lithium metal foil layers are converted into lithium-aluminum layers using aging / pre-lithiation.
[0089] In other examples, the anode electrode may comprise a rolled and annealed aluminum foil layer and a separator layer disposed on the opposite side of the lithium metal foil layer. The layers are mechanically bonded together using a similar process, and the lithium metal foil layer is converted into a lithium-aluminum layer using aging / pre-lithiation.
[0090] Now for reference Figure 4 The ASSB battery 200 includes C cathode electrodes 220, S separators 232, and A anode electrodes 240, where C, S, and A are integers greater than zero. The C cathode electrodes 220 include a cathode active material layer 224 and a cathode current collector 226. The cathode active material layer 224 includes a cathode active material 227 and a solid electrolyte 228. The S separators 232 include a solid electrolyte 233. The A anode electrode 240 includes an annealed aluminum layer 246 and a lithium aluminum (LiAl) layer 242 disposed on one or both sides thereof.
[0091] In some instances, the cathode electrode loading is 1 to 10 mAh / cm². 2 In some instances, the cathode electrode loading is 3 to 5 mAh / cm³. 2 (e.g., 4mAh / cm) 2 In some instances, the thickness of spacer 232 is from 5 μm to 150 μm. In some instances, the thickness of spacer 232 is from 30 μm to 50 μm (e.g., 40 μm).
[0092] In some instances, the annealed aluminum layer acts as both the active material and the current collector. In some instances, the thickness of the annealed aluminum layer ranges from 1 μm to 40 μm. In some instances, the thickness of the annealed aluminum layer ranges from 5 μm to 15 μm (e.g., 10 μm). In some instances, the grain boundary (GB) distribution (>150) of the annealed aluminum is 45% to 80%. In some instances, the grain boundary (GB) distribution (>150) of the annealed aluminum is 60% to 70% (e.g., 65%).
[0093] In some instances, a pretreated aluminum layer (LiAl layer) serves as both the anolyte and the lithium-ion conductor. In addition to the aluminum composition, the anolyte also contains 0.02 to 2.0 mg / cm³ of aluminum. 2 (e.g., 1.04 mg / cm) 2 Lithium. In some instances, the thickness ranges from 1 μm to 80 μm. In some instances, the thickness ranges from 30 μm to 50 μm (e.g., 40 μm).
[0094] Now for reference Figure 5 Except for the anode electrode, the ASSB battery 300 is similar to the ASSB battery 200. The ASSB battery 300 includes A anode electrodes 340, each anode electrode 340 including an annealed aluminum layer 342, a lithium aluminum (LiAl) layer 344 disposed on one side of the annealed aluminum layer 344, and an anode current collector 346 (e.g., a copper foil layer) disposed on one side of the LiAl layer 344. The opposite side of the anode current collector 346 may also include the LiAl layer 344 and the annealed aluminum layer 342.
[0095] Now for reference Figure 6 This disclosure can also be applied to other battery packs. Battery pack 400 includes C cathode electrodes 420, S separators 432, and A anode electrodes 440, where A, S, and C are integers greater than 1. The C cathode electrodes 420 include a cathode active material layer 424 and a cathode current collector 426. The cathode active material layer 424 includes a cathode active material 427 and a liquid electrolyte 428. The S separators 432 include separator layers, such as polymer layers. The A anode electrode 440 includes an annealed aluminum layer 446 and a lithium aluminum (LiAl) layer 442 disposed on one or both sides thereof.
[0096] Now for reference Figure 7 The battery pack 500 includes C cathode electrodes 520, S separators 532, and A anode electrodes 540, where A, S, and C are integers greater than 1. The C cathode electrodes 520 include a cathode active material layer 524 and a cathode current collector 526. The cathode active material layer 524 comprises a cathode active material 527 and a liquid electrolyte 528. The S separators 532 include a separator layer (e.g., a polymer layer). The A anode electrodes 540 include an annealed aluminum layer 542, a lithium aluminum (LiAl) layer 544, and an anode current collector 546 (e.g., a copper foil layer). As shown above, the opposite side of the anode current collector 546 may optionally include the LiAl layer 544 and the annealed aluminum layer 542.
[0097] Now for reference Figure 8The semi-solid-state battery pack 600 includes C cathode electrodes 620, S separators 632, and A anode electrodes 640, where A, S, and C are integers greater than 1. The C cathode electrodes 620 include a cathode active material layer 624 and a cathode current collector 626. The cathode active material layer 624 includes a cathode active material 627, a solid electrolyte 628, and a liquid electrolyte 629. The S separators 632 include a solid electrolyte 633 and a liquid electrolyte 629. The A anode electrode 640 includes an annealed aluminum layer 646 and a lithium-aluminum (LiAl) layer 642 disposed on one or both sides thereof.
[0098] Now for reference Figure 9 The semi-solid-state battery pack 700 includes C cathode electrodes 720, S separators 732, and A anode electrodes 740, where A, S, and C are integers greater than 1. The C cathode electrodes 720 include a cathode active material layer 724 and a cathode current collector 726. The cathode active material layer 724 includes a cathode active material 727, a solid electrolyte 728, and a liquid electrolyte 729. The S separators 732 include a solid electrolyte 733 and a liquid electrolyte 729. The A anode electrode 740 includes a lithium aluminum (LiAl) layer 742 and an annealed aluminum layer 746 disposed on one or both sides thereof.
[0099] Now for reference Figures 10 to 11B The pre-lithiation step triggers a spontaneous transition from the α phase (Al structure, face-centered cubic (fcc)) to the β phase (LiAl, cubic). The formed LiAl compensates for the loss of active lithium to enhance battery cycling. Figure 10 Aluminum atoms are shown at position 810, while lithium atoms are shown at position 812. Figure 11A and 11B The image shows aluminum foil before annealing (at 820°C) and after annealing (at 810°C). It can be seen that annealing adjusts the grain boundary distribution.
[0100] Now for reference Figure 12 Grain boundary diffusion is the fastest diffusion pathway. When Al-Al-GB transforms into LiAl-Al or LiAl-LiAl-GB (with dramatic GB slip), the phase transition alters the morphology of the grain boundaries (GB). Therefore, the free volume of GB increases in situ, thereby enhancing the diffusion capacity of Li along the GB to counteract future Li intrusion. For the diffusion of Li atoms at the LiAl / Al phase boundary (PB), the PB interface does not change significantly because the PB moves vertically and remains relatively unchanged (maintaining relatively low diffusion capacity). Compared to other pathways (phase boundaries, dislocation nuclei, or lattice), GB diffusion is the fastest diffusion pathway. Annealing of aluminum foil increases the GB distribution, thereby increasing lithium-ion diffusion.
[0101] Now for reference Figure 13 and14 The electrochemical properties of pre-lithiated aluminum foil were compared with those of annealed pre-lithiated aluminum foil. Figure 13 In the diagram, both battery packs include NCM721 as the cathode active material, a sulfide solid electrolyte, and an Al-LiAl anode electrode. Pre-lithiated aluminum foil is shown at 850°C, and pre-lithiated and annealed aluminum foil is shown at 860°C. Initial charge-discharge (e.g., at 0.1C charging and 25°C) show that the initial coulombic efficiency increases from 70% to 86% due to the annealed pre-lithiation, and the initial coulombic efficiency increases from 126 mAh / g to 143 mAh / g during 0.1C discharge. Figure 14 In the process, the performance increased from 99 mAh / g to 124 mAh / g during 0.2C discharge. This is due to the Li... + Enhanced diffusion pathways resulted in improved initial coulombic efficiency and increased capacity delivery in the annealed pre-lithiated aluminum foil.
[0102] In some instances, wet coating processes, dry film-forming processes, or other suitable processes are used to prepare the cathode active material layer. In some instances, the cathode active material layer comprises cathode material (30 to 98 wt%), optional solid electrolyte (1 to 50 wt%), and optional binder (1 to 20 wt%).
[0103] In some instances, the cathode active material includes layered oxides represented by the formula LiMeO2, olivine-type oxides represented by the formula LiMePO4, monoclinic oxides represented by the formula Li3Me2(PO4)3, spinel-type oxides represented by the formula LiMe2O4, tavorite represented by one or both of the following formulas LiMeSO4F or LiMePO4F, and / or combinations thereof, wherein Me is a transition metal (e.g., Co, Ni, Mn, Fe, Al, V, or combinations thereof). In some instances, the cathode active material includes sulfur or Li2S. In some instances, the above-mentioned cathode active materials are coated with a coating (e.g., LiNbO3 and Li3PO4).
[0104] In some examples, adhesives include polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene-ethylene-butene-styrene copolymer (SEBS), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), polyacrylonitrile (PAN), polyacrylic acid (PAA), styrene-butadiene-styrene copolymer (SBS), etc.
[0105] In some instances, the solid electrolyte is selected from sulfide solid electrolytes, oxide-based solid electrolytes, metal-doped or anisovalent substituted oxide solid electrolytes, nitride-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and borate-based solid electrolytes.
[0106] Examples of sulfide solid electrolytes include pseudo-binary sulfides, pseudo-ternary sulfides, and pseudo-quaternary sulfides. Examples of pseudo-binary sulfides include the Li₂S-P₂S₅ system (Li₃PS₄, Li₇P₃S₅). 11 and Li 9.6 P3S 12 Examples of pseudo-ternary sulfides include the Li2S-SnS2 system (Li4SnS4), Li2S-SiS2 system, Li2S-GeS2 system, Li2S-B2S3 system, Li2S-Ga2S3 system, Li2S-P2S3 system, and Li2S-Al2S3 system. Examples of pseudo-ternary sulfides include the Li2O-Li2S-P2S5 system, Li2S-P2S5-P2O5 system, Li2S-P2S5-GeS2 system, and (Li... 3.25 Ge 0.25 P 0.75 S4 and Li 10 GeP2S 12 ), Li2S-P2S5-LiX system (X=F, Cl, Br, I) (Li6PS5Br, Li6PS5Cl, L7P2S8I and Li4PS4I), Li2S-As2S5-SnS2 system (Li 3.833 Sn 0.833 As 0.166 S4), Li2S-P2S5-Al2S3 system, Li2S-LiX-SiS2 system (X=F, Cl, Br, I), 0.4LiI·0.6Li4SnS4 and Li 11 Si2PS 12 Examples of pseudo-quaternary sulfides include the Li₂O-Li₂S-P₂S₅-P₂O₅ system, Li… 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 Li7P 2.9 Mn 0.1 S 10.7 I 0.3 and Li 10.35 [Sn 0.27 Si 1.08 ]P 1.65 S 12 .
[0107] Examples of oxide-based solid electrolytes include garnet-type electrolytes (e.g., Li7La3Zr2O). 12 ), perovskite type (e.g., Li), 3x La 2 / 3-x TiO3), NASICON type (e.g., Li) 1.4 Al 0.4 Ti 1.6 (PO4)3 and Li 1+x Al x Ge 2-x (PO4)3) and LISICON type (e.g., Li 2+2x Zn 1-x GeO4).
[0108] Examples of metal-doped or anisovalently substituted oxide solid electrolytes include Al (or Nb)-doped Li7La3Zr2O 12 Sb-doped Li7La3Zr2O 12 Ga-substituted Li7La3Zr2O 12 LiSn2P3O substituted with Cr and V 12 Al-substituted perovskites and Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 Examples of nitride-based solid electrolytes include Li3N, Li7PN4, and LiSi2N3. Examples of hydride-based solid electrolytes include LiBH4, LiBH4–LiX (X = Cl, Br, or I), LiNH2, Li2NH, LiBH4–LiNH2, and Li3AlH6. Examples of halide-based electrolytes include LiI, Li3InCl6, Li2CdCl4, Li2MgCl4, Li2CdI4, Li2ZnI4, and Li3OCl. Examples of borate-based solid electrolytes include Li2B4O7 and Li2O–B2O3–P2O5.
[0109] In some instances, the solid electrolyte layer comprises a solid electrolyte (in the range of 20% to 100% by weight), an optional conductive filler (in the range of 1% to 30% by weight), and an optional binder (in the range of 0% to 20% by weight).
[0110] In some instances, the conductive filler is selected from oxide particles (e.g., SiO2, Al2O3, TiO2, ZrO2), polymer skeletons (e.g., polypropylene (PP), polyethylene (PE), lithium salts (e.g., LiTFSI, LiBF4)) or other suitable conductive fillers.
[0111] In some instances, the adhesive is selected from polyvinylidene fluoride (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP), polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), nitrile rubber (NBR), styrene-ethylene-butene-styrene copolymer (SEBS), polyethylene oxide (PEO), polyvinylpyrrolidone (PVP), polyvinyl alcohol, and polyacrylic acid (PAA).
[0112] In some instances, the thickness of the solid electrolyte ranges from 5 μm to 200 μm. It is understood that the solid electrolytes in the cathode active material layer, the solid electrolyte layer, and the anode layer can be the same or different.
[0113] In some instances, the porosity of the separator layer is between 5% and 100%. In some instances, the porosity of the separator layer is between 85% and 95% (e.g., 90%). In some instances, the separator layer is wetted by a liquid electrolyte.
[0114] In some instances, the spacer layer comprises a polyolefin-based spacer (e.g., polyacetylene: polypropylene (PP), polyethylene (PE), bilayer type: PP-PE, trilayer type: PP-PE-PP). In some instances, the spacer layer comprises a cellulose spacer, a polyvinylidene fluoride (PVDF) membrane, a porous polyimide membrane, and / or a ceramic-coated spacer (e.g., SiO2-coated PE).
[0115] In some instances, the insulating layer includes high-temperature stable insulating materials, such as nonwoven fabrics based on polyimide (PI) nanofibers, polyethylene films coated with nano-scale Al2O3 and poly(lithium 4-styrene sulfonate), SiO2-coated polyethylene (PE) insulating materials, copolyimide-coated polyethylene insulating materials, polyetherimide (PEI) (bisphenol acetone-phthalic anhydride (BPADA) and p-phenylenediamine) insulating materials, expanded polytetrafluoroethylene-reinforced polyvinylidene fluoride-hexafluoropropylene insulating materials, sandwich-structured PVdF / PMIA / PVdF nanofiber insulating materials, etc.
[0116] The foregoing description is merely exemplary and is in no way intended to limit this disclosure, its application, or its use. The broad teachings of this disclosure can be implemented in various forms. Therefore, although this disclosure includes specific examples, its true scope should not be limited thereto, as other modifications will become apparent upon examination of the drawings, specification, and the following claims. It should be understood that one or more steps within the method may be performed in a different order (or simultaneously) without altering the principles of this disclosure. Furthermore, although the embodiments are described above as having certain features, any one or more features described with respect to any embodiment of this disclosure may be implemented in any other embodiment and / or combined with features of any other embodiment, even if such combination is not explicitly described. In other words, the embodiments are not mutually exclusive, and substitution of one or more embodiments for each other remains within the scope of this disclosure.
[0117] Various terms are used to describe spatial and functional relationships between components (e.g., between modules, circuit elements, semiconductor layers, etc.), including “connection,” “joint,” “coupled,” “adjacent,” “next to,” “on top of,” “above,” “below,” and “disposed.” Unless explicitly described as “direct,” when describing the relationship between the first and second components in the foregoing disclosure, the relationship can be a direct relationship in which no other intermediary components exist between the first and second components, or an indirect relationship in which one or more intermediary components exist between the first and second components (spatially or functionally). The phrase “at least one of A, B, and C” as used herein should be interpreted as referring to the logic of OR (A or B or C) using non-exclusive logic, and should not be interpreted as referring to “at least one of A, at least one of B, and at least one of C.”
Claims
1. A battery pack comprising: C cathode electrodes; A anode electrode; and There are S isolation components, where A, C, and S are integers. Each of the A anode electrodes comprises: Annealed aluminum foil layer; and A lithium-aluminum layer disposed on one side of the annealed aluminum foil layer.
2. The battery pack according to claim 1, wherein... The S separators contain solid electrolytes. The C cathode electrodes include a cathode active material layer disposed on one or both sides of the cathode current collector, the cathode active material layer comprising cathode active material and solid electrolyte.
3. The battery pack according to claim 2, wherein the solid electrolyte is selected from sulfide solid electrolytes, oxide-based solid electrolytes, metal-doped or anisovalent substituted oxide solid electrolytes, nitride-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, borate-based solid electrolytes, and combinations thereof.
4. The battery pack according to claim 2, wherein the battery pack comprises an all-solid-state battery pack.
5. The battery pack according to claim 1, wherein... The S separators comprise solid electrolytes and liquid electrolytes. The C cathode electrodes each include a cathode active material layer, which comprises a cathode active material, a solid electrolyte, and a liquid electrolyte. The cathode active material layer is arranged on one or both sides of the cathode current collector.
6. The battery pack according to claim 5, wherein the solid electrolyte is selected from sulfide solid electrolytes, oxide-based solid electrolytes, metal-doped or anisovalent substituted oxide solid electrolytes, nitride-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, borate-based solid electrolytes, and combinations thereof.
7. The battery pack according to claim 1, wherein... The C cathode electrodes each include a cathode active material layer, the cathode active material layer comprising a cathode active material and a liquid electrolyte; and The S isolation components include isolation component layers.
8. The battery pack according to claim 7, wherein the separator layer is selected from polyolefin-based separators, cellulose separators, polyvinylidene fluoride (PVDF) membranes, porous polyimide membranes, and ceramic-coated separators.
9. The battery pack according to claim 7, wherein the separator layer is selected from nonwoven fabric based on polyimide (PI) nanofibers, polyethylene film coated with nano-scale Al2O3 and poly(lithium 4-styrene sulfonate), polyethylene (PE) separator coated with SiO2, polyethylene separator coated with copolyimide, polyetherimide (PEI) separator, expanded polytetrafluoroethylene reinforced polyvinylidene fluoride-hexafluoropropylene separator, and sandwich structure PVdF / PMIA / PVdF nanofiber separator.
10. The battery pack according to claim 1, wherein the C cathode electrodes comprise cathode active materials selected from layered oxides, olivine oxides, monoclinic oxides, spinel oxides, tavorite, sulfur, Li2S, and combinations thereof.